Movimentos e processos de desenvolvimento profissional contínuo na relação escola-universidade-escola : análise de uma prática realizada no oeste do Pará - Castro, Cláudia Silva de (2018)
This work is focused in discussions about in-service training and professional development through collaborative practices between school-university-school. The actions developed in this research are based on the scope from an institutional project from the Federal University of the West of Pará - UFOPA that is joined to the New Talents Program / CAPES, which a partnership with a state school in Santarém-PA through the Innovative Secondary Education Program / PROEMI. The central issue in this research is based on: Which guiding elements for the construction of in-services training practices emerge from the processes of Continuous Professional Development in the school-university-school relationship? On this, the goal is to investigate processes of Continuing Professional Development in-service training practices through the partnership and collaboration between school and university. The theoretical assumptions of this research are based on Ivor Goodson, Michael Fullan, Marcelo Garcia, António Nóvoa, Dário Fiorentini, António Cachapuz, Christopher Day and other authors, who discuss teacher education is based on the professional development processes. We adopted the qualitative research on the perspective of the research-action collaborative, which is based on theory of Jhon Elliot, Graça Mizukami, Ivana Ibiapina e Júlio Diniz-Pereira. In addition, it is based on a set of study-training activities about Educational Policies and on the development of integrative projects for the Scientific Initiation in the school. We consider as research cut the period between 2014 and 2017. The actions were developed through articulated work including training cycles, study and research groups at the school, on the interface with the university, study and planning meetings, collective training meetings, among others. The research participants were teachers, educational technicians, managers, and collaborators in the actions and representatives of other institutions that participated in the activities developed within the group. The analyzed corpus are consisted of audio records, videos, field notes, testimonials, narrative interviews and materials produced along the actions (projects, reports, narratives, etc.), which ones were organized in a Research Inventory. The analysis was based on Discursive Textual Analysis. On the elaboration of the metatext it was adopted the polyphonic narrative. The approximation and distance processes between school and university have indicated that those are produced along the route of training and professional performance, as well as production contexts both the school and university. In the school, the distances have happening on the professional insertion in teaching, on the internships period, on the context of institutional projects, on the interinstitutional articulation, the latter being also produced in the university, plus the specific disciplines of the undergraduate curriculum. We identified, as approximation spaces, the articulation between initial and continued formation and the professional performance, besides the institutional programs with participation of professionals of the school. In the process of establishing of partnership and setting up the Study and Research Group at the school, we identified as mobilizers of approach between school and university factors, such as: interests and needs of the school institution, Educational Policies elements and convergences between school and university in terms of actions and potential of continuous training in context. The studies at around Educational Policies have triggered learning about the pedagogical dimension, curricular domains, critical view of the policies in context and awaken motivations for learning, values and virtues professional. The work with projects of Scientific Initiation led to the integration of subjects, processes and pedagogical actions, reconstruction of learning processes, mobilization and renewal of professional learning, development of attitudes, values, virtues and foresight, besides professional and institutional strengthening. In view of the findings research, we argue that: The practices of contextual training, particularly in study group and research at school form, in partnership and collaboration between school and university constitute a promising way for the development of the schooluniversity-school relationship. This relationship has become stronger and successful, as both institutions take partnership and collaboration, the expanded and integrating Scientific Initiation and Continuous Professional Development as formative aspects in order to provide personal, professional and interinstitutional approximations and (trans) formations. It is constituted in a cyclical and continuous perspective having as central elements: transformation, innovation, axiological dimension and continuity. We believed that this investigation can contribute to: a) study and collaborative practice of continuous training in context; b) training policies related to the articulation between school and university; c) to develop the scientific education vision expanded and inclusive, involving the different professionals of the school collective the integration between different areas of knowledge at around interdisciplinary scientific education practices; d) interinstitutional spaces favorable to the strengthening of personal/professional dimensions and institutions under multiple perspectives; and e) to promote the integration of the different visions surpluses of school and university professionals around the field of school practices and Educational Policies, the theoretical field of teacher and scientific education, and teaching and learning processes in the school.